An unusual new genus and species of Hecalini leafhopper from southern China (Hemiptera: Cicadellidae: Deltocephalinae) - He, Zhi-Qiang; Zhang, Ya-Lin; Webb, Michael D. (Zootaxa, 2008)
An interesting new genus and species of Hecalini leafhopper, Hecalusina unispinosa, sp. n., are described from southern China. The unusual features of the new genus, including the male and female genitalia, are discussed and compared to other Hecalini.